A phase 1 study to evaluate the safety and LDL cholesterol–lowering effects of RG7652, a fully human monoclonal antibody against proprotein convertase subtilisin/kexin type 9. Issue 7 (22nd March 2017) - Baruch, Amos; Luca, Diana; Kahn, Robert S.; Cowan, Kyra J.; Leabman, Maya; Budha, Nageshwar R.; Chiu, Cecilia P.C.; Wu, Yan; Kirchhofer, Daniel; Peterson, Andrew; Davis Jr, John C.; Tingley, Whittemore G.
Abstract : Background: Proprotein convertase subtilisin/kexin type 9 (PCSK9) downregulates low‐density lipoprotein (LDL) receptors, thereby leading to a rise in circulating LDL cholesterol (LDL‐C). RG7652 is a fully human monoclonal antibody against PCSK9. This placebo‐controlled, phase 1 ascending‐dose study in healthy subjects evaluated the safety of RG7652 and its efficacy as a potential LDL‐C–lowering drug. Hypothesis: Anti‐PCSK9 antibody therapy safely and effectively reduces LDL‐C. Methods: Subjects (N = 80) were randomized into 10 cohorts. Six sequential single‐dose cohorts received 10, 40, 150, 300, 600, or 800 mg of RG7652 via subcutaneous injection. Four multiple‐dose cohorts received 40 or 150 mg of RG7652 once weekly for 4 weeks, either with or without statin therapy (atorvastatin). Results: Adverse events (AEs) were generally mild; the most common AEs were temporary injection‐site reactions. No serious AEs, severe AEs, AEs leading to study‐drug discontinuation, or dose‐limiting toxicities were reported. RG7652 monotherapy reduced mean LDL‐C levels by up to 64% and as much as 100 mg/dL at week 2; the effect magnitude and duration increased with dose (≥57 days following a single RG7652 dose ≥300 mg). Exploratory analyses showed reduced oxidized LDL, lipoprotein(a), and lipoprotein‐associated phospholipase A2 with RG7652. Antidrug antibody against RG7652 tested positive in 2 of 60 (3.3%) RG7652‐treated and in 4 of 20 (20.0%) placebo‐treated subjects. Simultaneous atorvastatin administration did not appear to impact the pharmacokinetic profile or lipid‐lowering effects of RG7652. Conclusions: Overall, RG7652 elicited substantial and sustained dose‐related LDL‐C reductions with an acceptable safety profile and minimal immunogenicity.